Effect of Some Types of Anticoagulants on Some Biochemical Parameters of Plasma In Atherosclerosis Disease - Abeer Talib. Abdulqader; Muhaned. E. Majeed; Wijdan I. A. Abd-alwahab (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This study investigated the influence of anticoagulant therapy on biochemical parameters and vascular function in patients with mixed dyslipidemia and asymptomatic atherosclerosis. Twenty-five participants were divided into two groups: a study group (SG) of 15 patients with mixed dyslipidemia and a control group (CG) of 9 healthy individuals. Baseline characteristics, including lipid profiles, inflammatory markers (osteopontin, osteoprotegerin, MMP-2, MMP-9), and clotting parameters, were assessed. The SG exhibited significantly elevated levels of total cholesterol, LDL cholesterol, non-HDL cholesterol, and triglycerides, alongside decreased HDL cholesterol and unexpectedly lower myeloperoxidase levels compared to the CG. Significant variability in biomarker levels was observed across quartiles within both groups. A strong positive correlation was found between serum TSH levels and Factor X activity, while a strong negative correlation was observed between serum TSH and PAI-1 antigen levels in patients with subclinical hyperthyroidism. Clotting times, assessed using the thromboplastin generation test with inosithin, did not reveal significant differences between venous and arterial samples or between the study and control groups based on the provided data. Further research incorporating quantitative clotting time analyses and a more comprehensive assessment of anticoagulant effects is needed to elucidate the complex interplay between anticoagulant therapy, dyslipidemia, and atherosclerosis.